Performance of the dental surgeon in promoting oral health in indigenous communities (Research, Society and Development, 2023)
The general panorama of oral health among indigenous peoples is marked by complexity and precariousness, the promotion of which has been historically neglected. It is identified as extremely necessary to deepen and present reflections on the benefits of action and the challenges that dentistry professionals face in promoting oral health in indigenous communities. Given this context, this research aimed to present the role of the dental surgeon in promoting oral health in indigenous communities, its difficulties and limitations. To achieve this purpose, a literature review was carried out in which the search was carried out in databases such as PubMed, Scientific Electronic Library Online (SciELO), Virtual Health Library - Dentistry and Google Scholar. From the current literature it is possible to identify that there are many difficulties and limitations for the dentist's role in promoting the oral health of aboriginal peoples. The problem is generally complex. And this is due not only to the large number of problems, but also to the different factors involved, ranging from the negligence of the competent authorities regarding the allocation and availability of resources to geographical, cultural and linguistic issues. The role of the dental professional ends up being compromised. This scenario highlights the need for public policies, actions and measures that are reflected in the real situation in which native peoples live, and for oral health education and promotion strategies that are capable of conditioning as well as reinforcing dental care in indigenous communities.